Rheological characteristics of steel in continuous roll casting-rolling - Ольга Холявік; Олексій Ноговіцин; Олексій Кравчук; Олексій Самойленко; Руслан Борис (Mechanics and Advanced Technologies)
Problems. In the process of obtaining a strip in a casting and rolling device, the question arises of combining the process of hot rolling of the solidified material and the process of crystallization of the liquid melt. This makes it possible to implement an efficient technology for producing thin-sheet products.